Germination of native and introduced plants from scats of Fallow Deer (Dama dama) and Eastern Grey Kangaroo (Macropus giganteus) in a south‐eastern Australian woodland landscape. (21st January 2016) - Claridge, Andrew W.; Hunt, Rob; Thrall, Peter H.; Mills, Douglas J.
Summary: Introduced deer occur in many forests and woodlands in Australia and potentially play an important role in influencing the floristics and structure of these landscapes through eating plants and disseminating seeds. In a glasshouse trial, we tested whether field‐collected scats of Fallow Deer ( Dama dama ) contained viable plant seeds. Scats of deer obtained from a woodland study area in Kosciuszko National Park, New South Wales, produced seedlings from a range of native and introduced plant species. Forbs and herbs were dominant in these samples, confirming the grazing behaviour of deer at the time scats were collected. Samples of scats from Eastern Grey Kangaroos ( Macropus giganteus ), collected contemporaneously from the same sites as deer scats, also produced plant germinants. By volume, deer scats produced a greater diversity of plant germinants, including native and weed species, than did kangaroo scats. Although no weed species emanating from deer or kangaroo scats were of national significance, several species were of regional environmental significance, including Common Mullein ( Verbascum thapsis ), which was only found germinating out of deer scat, Stinkgrass ( Eragrostis cilianensis ) and Purpletop ( Verbena bonariensis ). In addition to dispersing viable seeds, Fallow Deer may also influence vegetation structure through their browsing. Further research is necessary to elucidate their respective role in dispersing native and introduced plants as well as any impacts that foraging behaviour might be having on woodland landscapes, to better inform management of the resident deer population.